2017
DOI: 10.4103/ijmm.ijmm_17_299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin-28B Polymorphism on Interleukin-28 Expression and Immunological Recovery amongst HIV-1-Infected Individuals Following Antiretroviral Therapy

Abstract: Our preliminary findings suggest that IL-28 polymorphisms could influence both immunological recovery and therapeutic response in HIV infection. Hence, functional studies are warranted to understand the mechanistic basis of IL-28-mediated host genetic influence on HIV therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…As in viral hepatitis, certain IFN-λ3/λ4 polymorphisms were associated with HIV resistance [42], while others increased susceptibility to acquired immunodeficiency syndrome-related Kaposi sarcoma [43]. Moreover, IFN-λ3 polymorphisms can influence both immunologic recovery and therapeutic response in HIV infection [44]. These observations provide evidence supporting the…”
Section: Human Immunodeficiency Virusmentioning
confidence: 70%
“…As in viral hepatitis, certain IFN-λ3/λ4 polymorphisms were associated with HIV resistance [42], while others increased susceptibility to acquired immunodeficiency syndrome-related Kaposi sarcoma [43]. Moreover, IFN-λ3 polymorphisms can influence both immunologic recovery and therapeutic response in HIV infection [44]. These observations provide evidence supporting the…”
Section: Human Immunodeficiency Virusmentioning
confidence: 70%
“…included a very good size study population it was a heterogeneous cohort which is not ideal for genetic studies (14). In contrast, others have found the rs12979860 CC genotype to have a beneficial effect on HIV disease progression (15, 20). While Machmach et al found an over-representation of the rs12979860 CC genotype among HIV controllers compared to non-controllers (15), Srinidhi et al showed the CC genotype to be associated with increased CD4 T cell count following ART initiation (20).…”
Section: Discussionmentioning
confidence: 91%
“…По данным W. Hou и соавт., ИЛ-28В способен влиять на ВИЧ путем ингибирования репликации посредством внутриклеточных и внеклеточных механизмов [10]. Результаты исследований последних лет поддерживают теорию о контроле обеих инфекций с участием ИЛ-28В [11], а также указывают на связь между полиморфизмом гена ИЛ-28В и иммунологическим ответом у ВИЧ-инфицированных пациентов на антиретровирусной терапии (АРВТ) [12].…”
unclassified